Upaya Meningkatkan Hasil Belajar Matematika Tema 1 Diriku pada Peserta Didik Kelas I B SD Negeri Kasreman Melalui Permainan Scrabble di Semester I Tahun Pelajaran 2018/2019 - Saptaningrum Saptaningrum (Universitas Sebelas Maret, 2019)
The type of this research is a Class Action Research (CAR) with the purpose toanalyze the Mathematic learning outcome on the First Chapter about Myself of the students ofClass I B the Elementary School of Kasreman with the scrabble game on the first Semester ofthe 2018/2019 year academic. The subjects of this research are the students of Class I B theElementary School of Kasreman on the first Semester of the 2018/2019 year academic as muchas twenty three children; consist of ten boys and thirteengirls. The data resources of thisresearch are relating with learning activities and learning outcomes. Techniques of collectingdata of this research are non test technique and test technique. Technique of analyzing data ofthis research is comparative description. The procedure of this research is the Kemmis and McTaggart’s cycle model. The results of this research are 1) the Mathematic learning on the FirstChapter about Myself with the scrabble game is a group task, 2) the Mathematic learnings onthe First Chapter about Myself with the scrabble game are a practically simple rules, 3) theMathematic learning on the First Chapter about Myself with the scrabble game areincreasingthe learning activities in actively discussing, cooperating collaboration, very activelyanswering the questions form the teacher and other students, very actively asking the questionsand 4) the Mathematic learning outcomes on the First Chapter about Myself with the scrabblegameare increasing. The learning outcomes on the Early Condition are 53,91 for the averageand 30,43% for the completeness. The learning outcomes on the First Cycle are 69,56 for theaverage and 65,21% for the completeness. The learning outcomes on the Second Cycle are82,6 for the average and 86,95% for the completeness.